The intended and unintended consequences of remote working: Narratives from a sample of female public service managers in South Africa - Chinyamurindi, Willie Tafadzwa (Frontiers in Psychology, 2022)
The COVID-19 pandemic has affected the world of work. Stemming from this, new forms of work arrangements are proposed. One such arrangement concerns the use of remote working. Scholars appeal for more empirical inquiry into such work arrangements as an unintended consequence of the COVID-19 pandemic. The study narrows its focus to investigating remote working experiences from the lens of female middle managers operating within the South African public service. A qualitative research approach utilizing narrative inquiry of 23 female middle managers was used. Based on the analyzed data, remote working is illustrated from the participant experience as having intended and unintended consequences. In illustrating these dual consequences is a nexus between opportunities and challenges. Based on the identified intended and unintended consequences as findings, interventions have been proposed that impact not just the experience of being a middle manager in the public service but also strategies in dealing with remote working. At the core are strategies for individuals and organizations. These strategies potentially allow for middle manager contributions to be enhanced while also enhancing organizational outputs while working from home.